The integration of green chemistry principles in basic chemistry learning to support achievement of Sustainable Development Goals (SDGs) through education - Mitarlis Mitarlis; Utiya Azizah; Bertha Yonata (OmniaScience, 2023)
Recently the trend of words in the world is related to sustainable development such as "green" has become a new trend in everyday human life.  This study aimed to analyze and map the chemistry learning with green chemistry insight for undergraduate students of chemistry education program as an effort to conserve the environment as one of the Sustainable Development Goals (SDGs). The urgency of this study is to support the achievement of SDGs through education, especially the target number 12, responsible consumption and production and/or number 13, climate action. Data collection was used in exploratory method by combining primary and secondary exploratory framework. The primary method was focused on the observation qualitative or quantitative and the secondary on the literature research.  Data analysis were used qualitative and quantitative descriptive.  It can be concluded that; the efforts to preserve the environment through education can be pursued with green chemistry insight learning. The principles of green chemistry that can be implemented in chemistry learning on suitable material represent in some action such as; waste prevention, use the safe solvent, energy efficiency, and creating safe and secure conditions for learning both in the classroom and laboratory. Chemistry learning have the role to support SDGs through education by using some learning model/methods, such as discussion, concept map, or practical methods as well as Project Based Learning. So, the results of this study can be referred as an alternative learning that have contribution in SDGs achievement through education.